2014
DOI: 10.4081/bam.2014.2.75
|View full text |Cite
|
Sign up to set email alerts
|

Functional electrical stimulation on paraplegic patients

Abstract: Functional Electrical Stimulation on Paraplegic Patients. We report on clinical and physiological effects of 8 months Functional Electrical Stimulation (FES) of quadriceps femoris muscle on 16 paraplegic patients. Each patient had muscle biopsies, CT-muscle diameter measurements, knee extension strength testing carried out before and after 8 months FES training. Skin perfusion was documented through infrared telethermography and xenon clearance, muscle perfusion was recorded through thallium scintigraphy. Afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 29 publications
(32 reference statements)
0
8
0
Order By: Relevance
“…[6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] The benefits of this technology are being expanded into other areas, and FES has been recently utilized for injury rehabilitation and performance enhancement in horses. [24][25][26][27] The ability of FES to obtain precise, controlled functional movement, when compared to other electrotherapy approaches, is intriguing.…”
Section: Functional Electrical Stimulation (Fes) Has Beenmentioning
confidence: 99%
See 1 more Smart Citation
“…[6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] The benefits of this technology are being expanded into other areas, and FES has been recently utilized for injury rehabilitation and performance enhancement in horses. [24][25][26][27] The ability of FES to obtain precise, controlled functional movement, when compared to other electrotherapy approaches, is intriguing.…”
Section: Functional Electrical Stimulation (Fes) Has Beenmentioning
confidence: 99%
“…The increases in mitochondrial density and distribution could be the result of the adaptive mechanisms of the muscle fibers to the increased number of contractions per week and of the associated increase in muscle perfusion. 6,7 In conclusion, the present data from the histological evaluation of the equine longissimus lumborum muscle pre and post 22 treatments of FES over a period of 8 weeks shows that: 1) As expected for the type of FES treatment used in this study, only a couple of horses showed significant increases in mean muscle fiber size when Pre-vs Post-FES biopsies were compared; 2) In the older horses, there were sparse (or many in one horse) very atrophic and angulated muscle fibers in both Pre-and Post-FES samples, whose attributes and distribution suggests that they were denervated due to a distal neuropathy; 3) The hypothesis of generalized FES-induced muscle fiber damage during epaxial muscle training is not supported by our data since: 3.1) Denervated muscle fibers were also present in the Pre-FES biopsies and 3.2) Only one horse presented many long-term denervated muscles fibers Post-FES; 4) Preliminary data indicate an increased density and distribution of mitochondria in Post-FES biopsies, suggesting that the clinical improvements in the FES treated horses may be related to daily increased muscle contraction and perfusion induced by FES training. Finally, we stress that FES treatment, as here provided, is a safe rehabilitation strategy in the management of equine epaxial muscle spasms and provides clinical improvements and some structural changes of the muscle tissue at the histological level.…”
mentioning
confidence: 99%
“…The increases in mitochondrial density and distribution could be the result of the adaptive mechanisms of the muscle fibers to the increased number of contractions per week and of the associated increase in muscle perfusion. 6 , 7 …”
Section: Discussionmentioning
confidence: 99%
“…The thesis is now reprinted in the special issues “The long-term denervated muscle”. 48 The English abstract is provided in the following paragraph.…”
Section: Helmut Kern: Pioneering Researchmentioning
confidence: 99%